Assessing Cognitive behavioural Therapy in Irritable Bowel (ACTIB): protocol for a randomised controlled trial of clinical-effectiveness and cost-effectiveness of therapist delivered cognitive behavioural therapy and web-based self-management in irritable bowel syndrome in adults. Issue 7 (15th July 2015) - Everitt, Hazel; Landau, Sabine; Little, Paul; Bishop, Felicity L; McCrone, Paul; O'Reilly, Gilly; Coleman, Nicholas; Logan, Robert; Chalder, Trudie; Moss-Morris, Rona
Abstract : Introduction: Irritable bowel syndrome (IBS) affects 10–22% of the UK population, with England's annual National Health Service (NHS) costs amounting to more than £200 million. Abdominal pain, bloating and altered bowel habit affect quality of life, social functioning and time off work. Current treatment relies on a positive diagnosis, reassurance, lifestyle advice and drug therapies, but many people suffer ongoing symptoms. Cognitive behaviour therapy (CBT) and self-management can be helpful, but availability is limited. Methods and analysis: To determine the clinical- and cost-effectiveness of therapist delivered cognitive behavioural therapy (TCBT) and web-based CBT self-management (WBCBT) in IBS, 495 participants with refractory IBS will be randomised to TCBT plus treatment as usual (TAU); WBCBT plus TAU; or TAU alone. The two CBT programmes have similar content. However, TCBT consists of six, 60 min telephone CBT sessions with a therapist over 9 weeks, at home, and two 'booster' 1 hour follow-up phone calls at 4 and 8 months (8 h therapist contact time). WBCBT consists of access to a previously developed and piloted WBCBT management programme (Regul8) and three 30 min therapist telephone sessions over 9 weeks, at home, and two 'booster' 30 min follow-up phone calls at 4 and 8 months (2½ h therapist contact time). Clinical effectiveness will be assessed by examining the difference between arms in the IBS Symptom Severity Score (IBS SSS) and Work and Social Adjustment Scale (WASAS) at 12 months from randomisation. Cost-effectiveness will combine measures of resource use with the IBS SSS at 12 months and quality-adjusted life years. Ethics and dissemination: This trial has full ethical approval. It will be disseminated via peer reviewed publications and conference presentations. The results will enable clinicians, patients and health service planners to make informed decisions regarding the management of IBS with CBT. Trial registration number: ISRCTN44427879.